The evolution and interrelations of the mass- and elite culture in the religious musical tradition - Lyaschenko, Iryna (Actual Problems of Mind, 2017)
The topic of this paper is the process of evolution of Christian musical culture from its sources up to modern sociocultural environment from the point of view of the manifestation of elite- and mass-culture. The evolution of religious musical culture is traced from «massness» through «elitarity» to synthetic «plurality» in the context of influence to the people and their possible orientation.